Analyzing the effects of social impacts of events on satisfaction and loyalty - Yuruk, Pinar; Akyol, Ayse; Simsek, Gulhayat Golbasi (ELSEVIER SCI LTD, 2017)
The purpose of this study is to examine the social impacts of events on participants' satisfaction and whether loyalty is a result of this satisfaction when taking attendance to event into consideration. This study uses data from a sample of 542 participants who participated in the Kirkpinar Oil Wrestling Festival. Factor analysis was performed, and the data was sorted into seven different categories: community benefits, cultural and educational benefits, quality of life concerns, community resource concerns, attendance to event, satisfaction, and loyalty. Structural equation modeling was performed, and the hypotheses were tested using bootstrap confidence intervals in addition to classical testing procedures. The hypothesis results showed a direct effect on quality of life concerns and attendance to event. In events on satisfaction, there was also a direct effect on loyalty. In addition, there was an indirect effect on quality of life concerns and attendance to events on loyalty through satisfaction. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Events; Social impacts of events; Attendance to events; Kirkpinar; Edirne; QUALITY-OF-LIFE; RESIDENTS PERCEPTIONS; CUSTOMER SATISFACTION; MEGA-EVENT; VARYING DEGREES; HOST COMMUNITY; FESTIVAL; INTENTIONS; MOTIVATION; MODEL; Environmental Sciences & Ecology; Social Sciences - Other Topics; Business & Economics